O processo de implantação da reforma do ensino médio (Lei 13.415/2017) na rede estadual de ensino do Amazonas - Gomes, Davilly Souza (Brasil, 2024)
The paper examines the implementation process of Law nº 13,415/2017 in the State of Amazonas. It is linked to the Training Itineraries and Life Projects in New High School project, developed by Rede JUVEM, with CNPq’s funding. The proposed section included the analysis of Resolutions of the State Education Council of Amazonas - CEE/AM, which are related to the Secondary Education Reform’s implementation. This is a documentary study with a qualitative approach. The results reveal the alignment of the state education department with national guidelines. The analysis of the CEE/AM resolutions demonstrates the adaptation of the local educational system through national legislative changes. It was found that the implementation of the secondary education reform in the state of Amazonas disregards regional specificities, deepens inequalities and is conducted in an authoritarian manner, excluding the participation of central actors at this level of education, namely students and( the teachers. The schedule designed based on the approval dates of the analyzed resolutions, as well as the lack of Opinions, considering that the approvals took place under the Ad Referendum regime, describes quick actions of a system that does not offer resistance to any of the proposals arising from Law 13,415 /2017. With approval processes contrary to the democratic rites expected from an important collegial body such as the State Education Council, these resolutions document that in Amazonas the process of implementing the High School Reform repeats authoritarian practices and the perspective of educational management of managerial nature, which violates at least two of the principles established in the 1988 Federal Constitution, namely the principle of democratic management of public education and the principle of guaranteeing quality standards.